US equity announcement risk premia - Lukas Petraseka; Jiri Kukacka (Charles University in Prague, Institute of Economic Studies (IES), 2024)
We analyze the announcement risk premia on the US market between September 1987 and March 2023 and find that the market index exhibits average excess returns of 8.3 bps for macroeconomic announcement days. This strongly contrasts with 1.4 bps returns for non-announcement days. We further measure the individual stocks' sensitivities to macroeconomic data announcements over various lookback periods and show that stocks in the high-sensitivity portfolios offer investors significantly higher returns than stocks in the low-sensitivity portfolios. The average returns on the difference portfolios amount to 18 bps per month for the 60-month sensitivities. The Fama-MacBeth regression coefficients for the announcement sensitivity are positive and statistically significant across all lookback periods.
Keywords: C58; G12; G14; 330; Asset pricing; macroeconomic data announcements; risk premia